Man and his environment - Singh, Indera P., 1928-; Tiwari, Surendra Chandra, 1928- (Xth ICAES series ;, 1980)
Selection of papers presented at the 10th International Congress of Anthropological and Ethnological Sciences, held at New Delhi in 1978.